Low plasma albumin levels are associated with increased plasma protein glycation and HbA1c in diabetes - Bhonsle, Hemangi S.; Korwar, Arvind M.; Kote, Sachin S.; Golegaonkar, Sandeep B.; Chougale, Ashok D.; Shaik, Mahemud L.; Dhande, Nitin L.; Giri, Ashok P.; Shelgikar, Kishore M.; Boppana, Ramanamurthy; Kulkarni, Mahesh J. (Journal of Proteome Research, 2012)
Albumin is one of the most abundant plasma proteins and is heavily glycated in diabetes. In this study, we have addressed whether variation in the albumin levels influence glycation of plasma proteins and HbA1c. The study was performed in three systems: (1) streptozotocin (STZ)-induced diabetic mice plasma, (2) diabetic clinical plasma, and (3) in vitro glycated plasma. Diabetic mice and clinical plasma samples were categorized as diabetic high albumin plasma (DHAP) and diabetic low albumin plasma (DLAP) on the basis of their albumin levels. For the in vitro experiment, two albumin levels, high albumin plasma (HAP) and low albumin plasma (LAP), were created by differential depletion of plasma albumin. Protein glycation was studied by using a combination of two-dimensional electrophoresis (2DE), Western blotting, and LC-MSE. In both mice and clinical experiments, an increased plasma protein glycation was observed in DLAP than in DHAP. Additionally, plasma albumin levels were negatively correlated with HbA1c. The in vitro experiment with differential depletion of albumin mechanistically showed that the low albumin levels are associated with increased plasma protein glycation and that albumin competes for glycation with other plasma proteins.
Keywords: advanced glycation end products (AGEs); Albumin; glucose; post translational modification